Conservation of woody species in China under future climate and land-cover changes - Peng, Shijia; Jian Zhang; Zhang, Xiaoling; Li, Yaoqi; Liu, Yunpeng; Wang, Zhiheng (Journal of Applied Ecology, 2021)
Abstract Climate and land-cover changes are major threats to biodiversity, and their impacts are expected to intensify in the future. Protected areas (PAs) are crucial for biodiversity conservation. However, their effectiveness under future climate and land-cover changes remains to be evaluated. Moreover, the impacts of climate and land-cover changes on multi-dimensions of biodiversity are rarely considered when expanding PAs. Using distributions of 8,732 woody species in China and species distribution models, we identified species that will be threatened by future climate and land-cover changes (i.e. species with significant projected loss of suitable habitats by the 2070s) under different dispersal scenarios. We then estimated the geographical patterns in species richness (SR) and phylogenetic diversity (PD) of threatened species, evaluated the effectiveness (i.e. the changes in SR and PD) of Chinese PAs and identified conservation priorities for future PA expansion. Approximately 12%–38% of woody species will be threatened under different scenarios. These species tend to be clustered in the tree of life, and their SR and PD show consistent spatial patterns, being highest at low latitudes. PAs currently protect 90% of threatened species. However, their SR and PD of threatened species within PAs will decrease by 30%–40% by the 2070s, which reduces the PA effectiveness, especially for PAs at low elevations and those with low topographic heterogeneity and high natural vegetation loss. The conservation priorities identified from the SR and PD of the threatened species are mainly in mountains in southern China, the Yunnan-Guizhou Plateau and Taiwan Island. PA expansion and ecological corridors in these regions are needed to conserve threatened species. Synthesis and applications. We present a systematic study of the impacts of future climate and land-cover changes on the conservation status of woody species and PA effectiveness in China. Our results suggest that future climate and land-cover changes will reduce PA effectiveness, and the spatial prioritization of biodiversity conservation should consider the influences of future global changes on biodiversity. These results shed new light on the conservation priorities for the post-2020 expansion of PAs in China.